2017
DOI: 10.2196/mhealth.6021
|View full text |Cite
|
Sign up to set email alerts
|

Support for Sustainable Use of Personal Health Records: Understanding the Needs of Users as a First Step Towards Patient-Driven Mobile Health

Abstract: BackgroundThe tethering of a personal health record (PHR) to an electronic medical record (EMR) may serve as a catalyst in accelerating the distribution of integrated PHRs. Creating shared health records for patients and their health care professionals using self-administered functions of EMR-tethered PHRs is crucial to support sustainable use of the system.ObjectiveThis study assesses the factors related to active use of a self-administered function (Health Notes) in an EMR-tethered PHR (Health4U) in a tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…Characteristics of PHR adopters in our study are in line with findings from previous research: PHR registration and use was more frequent in women [ 42 , 65 - 67 ] and younger individuals [ 11 ], with lower registration rates and use being seen in people above 65 years [ 59 , 65 , 67 - 69 ]. The lower adoption by elderly patients should be further studied, as it may be associated with several different factors such as access and use of computers and the Internet, literacy, numeracy, and socioeconomic status [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Characteristics of PHR adopters in our study are in line with findings from previous research: PHR registration and use was more frequent in women [ 42 , 65 - 67 ] and younger individuals [ 11 ], with lower registration rates and use being seen in people above 65 years [ 59 , 65 , 67 - 69 ]. The lower adoption by elderly patients should be further studied, as it may be associated with several different factors such as access and use of computers and the Internet, literacy, numeracy, and socioeconomic status [ 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…As in other studies, we used heuristic definitions to characterize subgroups of adopters according to their use of the PHR [ 11 , 56 - 59 ]. We did not use log-ins as a proxy for PHR use and focused instead on the actual input of personal health information by individuals registered in the PHR.…”
Section: Methodsmentioning
confidence: 99%
“…Functionalities of ePHRs that provide solutions for personalized needs and requirements of chronic patients have important implications for their adoption and use, as also emerged in our review (17,19,74,91,107). One review suggested that features such as access to personal health data and general health information, communicating with providers and support groups, and receiving personal decision support were linked to empirical evidence of bene ts from ePHR-enabled self-management (19).…”
Section: Discussionmentioning
confidence: 76%
“…Functionalities of PHRs that provide solutions for personalized needs and requirements of chronic patients have important implications for their adoption and use, as also emerged in our review (16,18,74,91,106). One review suggested that features such as access to personal health data and general health information, communicating with providers and support groups, and receiving personal decision support were linked to empirical evidence of benefits from PHR-enabled self-management (18).…”
Section: Discussionmentioning
confidence: 85%